2001
DOI: 10.1080/01421590126487
|View full text |Cite
|
Sign up to set email alerts
|

Small group learning in the final year of a medical degree: a quantitative and qualitative evaluation

Abstract: The new undergraduate medical curriculum in Manchester uses problem-based learning (PBL) throughout the course. However, the major difference from other PBL schools is that in years 3 & 4 (phase 2) the students can use clinical experience when discussing the paper cases. The process is then developed further in year 5 (phase 3), in which there are no set PBL 'triggers' and students bring their own cases to the groups for discussion. In this study, we have explored what happens in the phase 3 (year 5) group ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…As in our own study, other research has found that the biggest risk in having clinicians facilitate small groups is a tendency to take over the group process either by directly questioning students (Gilkison, 2003;MacPherson et al, 2001;Silver and Wilkerson, 1991) or by teaching rather than encouraging student discovery and learning (Kaufman and Holmes, 1998;Wilkerson and Irby, 1998). Other problems with tutors identified in our study and the literature also points to inadequate amounts of guidance and feedback they give to students (O'Hanlon et al, 1995).…”
Section: Discussionsupporting
confidence: 65%
“…As in our own study, other research has found that the biggest risk in having clinicians facilitate small groups is a tendency to take over the group process either by directly questioning students (Gilkison, 2003;MacPherson et al, 2001;Silver and Wilkerson, 1991) or by teaching rather than encouraging student discovery and learning (Kaufman and Holmes, 1998;Wilkerson and Irby, 1998). Other problems with tutors identified in our study and the literature also points to inadequate amounts of guidance and feedback they give to students (O'Hanlon et al, 1995).…”
Section: Discussionsupporting
confidence: 65%
“…Already, our students link clinical experiences to their discussions of hypothetical problems (see http://www.parable.man.ac.uk). 11 Tutorial discussions that use real patients as their starting point have shown promise in 2 phases of our curriculum 12,13 . However, real situations too easily take teachers and learners across the theory−practice divide, so they concentrate on problem solving – or clinical expertise – at the expense of theoretical understanding.…”
Section: Discussionmentioning
confidence: 99%
“…After limited clinical exposure in Years 1 and 2, students continue thematic learning in Years 3 and 4, but now with clinical skills training and simultaneous community and hospital attachments to provide access to a breadth of clinical problems and contexts 9 . In Year 5, they have one‐to‐one attachments to clinicians and continue to attend group tutorials, but now use real patients as triggers for PBL 10 …”
Section: Methodsmentioning
confidence: 99%